The microbial communities and natural fermentation quality of ensiling oat (Avena sativa L.) harvest from different elevations on the Qinghai-Tibet Plateau - Bao, Yuhong; Yangzong, Zhaxi; Yuan, Zhenjie; Shi, Ruizhi; Feng, Ke; Xin, Pengcheng; Song, Tianzeng (Frontiers in Microbiology, 2023)
Abstract Ensiling whole-crop oat (Avena sativa L.) has attracted a growing interest in the Qinghai-Tibet Plateau. The study aimed to investigate the microbial community and chemical composition of fresh and ensiled oat harvested from six different elevations of the Qinghai-Tibet Plateau. The oat (A. sativa L. cv. Qingyin No.1) was planted in six different sites across arable regions of Qinghai-Tibet Plateau (BM, Bomi County; BY, Bayi County; DZ, Dazi County; BR, Biru County; SC, Suo County; SN, Seni County), where the elevation was in the range of 2800-4500 m above sea level (a. s. l.). Oat was harvested at the milk stage and ensiled for 90 d. The highest CP and lowest WSC were observed in fresh Oat from CN and BM, respectively, however, no distinct gradient trend in water-soluble carbohydrate (WSC) and crude protein (CP) concentrations along the elevation gradient. The lowest LAB counts in fresh Oat from the highest elevational regions of CN. After 90 d of ensiling, the pH in all oat silages was lower than 4.2, silages from SC and CN showed the lowest pH and butyric acid concentration, and higher lactic acid (LA) concentration. The Oat silage from BR underwent poor silage fermentation, indicated by the lowest LA concentration and the highest pH. The bimodal distribution of fungal diversity, bacterial diversity, and richness in fresh oat along the elevation gradient (2852-4447 m a.s.l) were observed. Dioszegia, Cladosporium, and Vishniacozyma were the prevalent fungal genus in fresh oat, while Wickerhamomyces, Candida, and Saccharomyces dominated the fungal communities of silages. Wickerhamomyces and Candida were the dominant genera in ensiled oat from BM and SC, respectively. Erwinia, Paenibacillus, Pseudomonas, Leuconostoc, and Exiguobacterium dominated the bacterial community of fresh Oat, while Lactobacillus and Kosakonia were the dominant bacterial genus in Oat silages. Pantoea was the most dominant bacterial genus in fresh oat from low-elevational regions (BM, BY, and DZ). It is concluded that all oat harvested from six different elevations were well fermented, and high-efficient LAB might be present in fresh oat sampled from high altitudes.